Optimization of Facilities and Infrastructure Management in Improving the Quality of Learning at Madrasah Ibtidaiyah - Enes, Utami Okta Ria; Asha, Lukman; Wanto, Deri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The school must also be able to maintain and care for the existing facilities and infrastructure. Thus, students can learn optimally and effectively thanks to school facilities and infrastructure. The aims of this study were (1) to describe how the Planning of Educational Facilities and Infrastructure at M.I.S. Guppi 13 Tasikmalaya, (2) to describe how the Procurement of Educational Facilities and Infrastructure at M.I.S. Guppi 13 Tasikmalaya, (3) to describe how the Maintenance of Facilities and Infrastructure Education at M.I.S. Guppi 13 Tasikmalaya, (4) to describe how efforts to improve the management of educational facilities and infrastructure should be carried out in the future. The method used is field research (field research), which uses a qualitative descriptive approach. This study has three data analysis steps: reduction, presentation of data (display data), and conclusion (Verification). The research results show several conclusions, one of which is that M.I.S. Guppi 13 Tasikmalaya focuses on the administration, provision, usage, and upkeep of educational infrastructure. However, the implementation may be improved even though infrastructure and educational facilities are crucial for supporting teaching and learning activities.